Theodore Roosevelt explorateur - Armelle Enders (Nuevo mundo - Mundos Nuevos, 2005)
From december 1913 to the end of april 1914, the former president of the United States Theodore Roosevelt led a scientific expedition across the Brazilian states of Mato Grosso and Amazonia. Its main purpose aimed at putting on the map a river then considered as "unknown", which took the name of "Roosevelt" after the conclusion of this dangerous journey. On the Brazilian side, the expedition was led by colonel Cândido Mariano Rondon, famous in his country both by his explorations of the wilderness and audacious politics towards Indians. When he came back in the northern hemisphere, Theodore Roosevelt used his Brazilian journey for the benefit of his own legend, but also spread the fame of the Brazilian military missions and its contribution to the progress of Civilization.